Indentation-Induced Shear Band Formation in Thin-Film Multilayers - Bigelow, Shannon; Shen, Yu-Lin (Frontiers in Materials, 2017)
We report an exploratory investigation into the cause of shear band formation in multilayer thin-films subject to nanoindentation. The material system considered here is composed of alternating aluminum (Al) and silicon carbide (SiC) nanolayers, atop a silicon (Si) substrate. Finite element models are developed in an attempt to reproduce the shear banding phenomenon observed experimentally. By introducing strain softening into the material model for the hard SiC layers, shear bands can be seen to emerge from the indentation site in the finite element analysis. Broad implications, along with possible directions for future work, are discussed.